Pattern-Recognition Receptors and Cervical Microbiome in Patients with Early Miscarriages - Mariya V. Gryaznova; Olesya N. Kozarenko; Victoria M. Ivannikova; Yuliya D. Smirnova; Inna Y. Burakova; Oxana B. Altukhova; Natalia I. Samborskaya; Mikhail Y. Syromyatnikov; Alexander Y. Maslov; Olga P. Lebedeva (Hindawi Limited, 2024)
Early miscarriages are one of the main causes of reproductive losses. The objective of this study was to estimate Toll- and NOD-like receptors mRNA expression levels and their correlation with microbiome composition in the endocervix of patients with 1st trimester miscarriages (n = 15) compared to those with healthy ongoing pregnancies (n = 15). Samples of the cervical epithelium were collected using a cytobrush. The expression of Toll-like receptors (TLR1, TLR2, TLR4, and TLR6) and NOD-like receptors (NOD1, NOD2, NLRP1, and NLRC4) was estimated by quantitative reverse-transcriptase PCR. Cervical microbiome composition was assessed by 16S rRNA next-generation sequencing. We found no differences in community state types (CSTs) and alpha- and beta-diversity between the groups. The dominant microorganisms in both groups were Lactobacillus iners. Bifidobacterium breve and Aeromonas popoffii, whose abundance was significantly higher in patients with miscarriages compared to those with ongoing pregnancies. Corynebacterium callunae and Turicibacter sanguinis, on the contrary, were significantly higher in women of the control group. Only decreased expression of TLR2 was observed in patients with miscarriages. The expression of other Toll- and NOD-like receptors showed no significant differences between the groups. NOD1 mRNA expression had a strong positive correlation with the abundance of L. iners, L. delbrueckii, and Aerococcus christensenii; TLR6 mRNA expression had a strong positive correlation with L. iners. The findings suggest that variations in Toll- and NOD-like receptors mRNA expression and specific shifts in the cervical microbiome might play a role in the immunological landscape, potentially contributing to the pathogenesis of early miscarriages.